Keyboard group teaching at the university and the popular repertoire: learning through hybrid practices (Per Musi, 2013)
This article presents examples of activities conducted in keyboard group classes in Brazil at Federal University of Pernambuco (UFPE), according to a hybrid approach that integrates deliberated practice (SANTIAGO, 2006) and informal learning practices (GREEN, 2001; 2008). The informal learning practice is a typical process of acquiring skills and knowledge by popular musicians, while deliberate practice generally comes from learning music in the classical context. In this study deliberate practice is used as an integral part of popular instrumental music learning. Four songs of specific teaching levels are presented, followed by a description of its working process.